Remarks on Receiving the 2001 Distinguished Service Award - Brian A. Burt, BDS, MPH, PhD (2001)
Thank you, Dushanka, for all those kind words. My first reaction on receiving the news of h s award was how privileged I am to be added to this list of the giants in our field. It is a signal honor that I appreciate deeply